Meta-Analysis the Effect of Pregnancy with Hepatitis B on Preterm Birth and Gestational Diabetes Mellitus - Haniah, Alfi Zamilul; Budihastuti, Uki Retno; Pamungkasari, Eti Poncorini (Journal of Maternal and Child Health, 2024)
Background: HBsAg positive pregnant women are responsible for around 50% of the global disease burden. Hepatitis B is caused by inflammation or infection of liver cells caused by the HBV virus. Pregnant women with hepatitis B can experience increased levels of cytokines which then cause pregnancy disorders. This study aims to examine the effect of pregnancy with hepatitis B on the incidence of preterm birth and Gestational Diabetes Mellitus (GDM). Subjects and Method: This study is a meta-analysis study and a systematic review. The articles used were obtained from several electronic databases including PubMed, Science Direct, Research Gate, and Google Scholar. The articles used in this study were articles that have been published from 2012-2022. The keywords to search for articles are as follows Pregnancy AND (“Hepatitis B” OR HBV OR HBsAg) AND (“pregnancy outcome” OR “fetal outcome”) AND (“preterm birth” OR “preterm delivery” OR premature) AND (“gestational diabetes mellitus” OR GDM). The researched article is a complete text with an observational study design. Articles were collected using the PRISMA diagram, and analyzed using the Review Manager 5.4 application. Results: A total of 14 prospective and retrospective cohort studies were analyzed. Articles were originated from China, Hong Kong, France and Botswana. Hepatitis B in pregnancy increased the risk of preterm birth (aOR=1.20; CI 95%=1.09 to 1.33; p<0.001) and gestational diabetes mellitus (aOR= 1.20; CI 95%= 1.12 to 1.28; p<0.001). Conclusion: Hepatitis B in pregnancy increases the risk of preterm birth and GDM significantly.